Health Literacy and Web-Based Audiovisual Multimedia in Pituitary and Endoscopic Skull Base Surgery - Gill, Amarbir S.; Biggs, Philip C.; Hagwood, Garrett; Beliveau, Angela M.; Shahlaie, Kiarash; Strong, E. B.; Steele, Toby O. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction The internet presents a rich milieu of multimedia options relating to pituitary and endoscopic skull base surgery (ESBS). Misinformation can create discordance between patient and provider expectations. The purpose of this study is to analyze the understandability and actionability of available ESBS and pituitary surgery audiovisual information on YouTube and Google.Methods The top 50 videos generated by searching “pituitary surgery/transsphenoidal surgery” and “endoscopic skull base surgery” in both YouTube and Google were sorted by relevance. Two independent reviewers evaluated each for understandability and actionability based on the Patient Education Materials Assessment Tool for audiovisual material (PEMAT-A/V). Source, authorship, audience, and education/advertisement variables were collected. Chi-square test followed by univariate and multivariate regression analyses assessed the association between these variables and quality.Results A total of 85 videos (52 YouTube and 33 Google) met inclusion criteria for analysis. There was no significant difference in the presence of the aforementioned variables between YouTube and Google (p < 0.05). Also, 72% of videos targeted patients and 28% targeted surgeons. Academic institutions uploaded 58% of videos. Surgeon-targeted videos were more educational (p = 0.01) and patient-targeted videos involved more advertisement (p = 0.01). Understandability and actionability scores were below the 70% threshold for both YouTube (65 ± 15, 38 ± 33, p = 0.65) and Google (66 ± 12, 38 ± 26, p = 0.94). Patient-targeted videos (p = 0.002) were more understandable, while surgeon- (p < 0.001) and education-focused videos (p < 0.001) were more actionable.Conclusion Understandability and actionability of YouTube and Google audiovisual patient information on ESBS and pituitary surgery is poor. Consideration should be given to the formation of a standardized patient information resource.
Keywords: endoscopic; endonasal; skull base; audiovisual; pituitary; health literacy